A vertical-mode extrapolation scheme applied to the Brazil Current domain: quasi-synoptic scenarios - João P. M. Amorim; João P. M. Amorim; Ilson C. A. da Silveira; Milton Borges-Silva; Pedro W. M. Souza-Neto; Wellington C. Belo; Cauê Z. Lazaneo; Piero S. Bernardo; Marcelo Dottori; Renato P. Martins; Daniel L. Moreira (Ocean and Coastal Research)
The Brazil Current (BC) is a western boundary current, with an average vertical extension of 500 m, which occupies the southwestern margin of Atlantic Ocean. Recently, the South Brazil Bight - SBB (23º S - 28º S) has been intensively explored by the oil and gas industries, which brought a high demand in operational oceanography and ocean state monitoring. In this study we present a new technique based on the vertical dynamic modes of oscillation, to extrapolate velocity profiles in the SBB, with potential applications to data acquired by Vessel Mounted Acoustic Doppler Current Profilers (VMADCP). Using four quasi-synoptic crosssectional velocity data, acquired by Lowered Acoustic Doppler Current Profilers (LADCP), we observed that the mean circulation of this region can be characterized as a 2-dynamical mode system. This mean circulation is mainly dominated at surface by the BC and at intermediate levels by the Intermediate Western Boundary Current (IWBC), which flows northward. Furthermore, observed mesoscale vortical features in the SBB, such as eddies and meanders, are shown to be primarily barotropic-mode dominated. In our extrapolation methodology, the use of an independent set of velocity time series obtained by four moorings has shown to be a valid way for obtaining the relative contribution of each dynamical mode in the velocity field in the SBB. Normalized mean squared errors below 10% and radar diagrams show that the presented methodology was able to reproduce the main dynamic features observed by LADCP transects. Also, with this technique, we extrapolated three VMADCP sections and the results agreed with previous observations.